Other Faces for Philosophy: Enlightenment prejudice and ordinary language - Olea Beltrán, Joaquín (2024)
This brief text outlines what is one of the most limiting vices of academic philosophy from the 19th century onwards: the total and naïve confidence in the capacities of pure reason and in the support of science. The choice of the date is based on the fact that the nineteenth century is "the century of the Enlightenment", and that behind this denomination there are hidden glimpses of disdain towards other periods and forms of thought. Starting from this problem, I delve into how the name was established with the use and abuse of ordinary language, and what are the effects of not conceiving the philosophical exercise outside the limits of "enlightened reason".